DIARY AND MEMOIRS OF MARKO CHEREMSHYNA IN THE CONTEXT OF THE MEMOIR HERITAGE OF THE FIRST HALF OF THE XXTH CENTURY - Fedun , M. R. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The subject of the attention of the author of this article were occupation diary of Marko Cheremshyna and his memoir portrait dedicated to Ivan Franko. It is proved that the national aspects of th memoirist's records, lyricism, sparkling folk humor, coloring of Hutsul narrator etc indicate the identity of memoirs works of the writer on the background of memoir heritage of the first decades of the XXth century.